Facilitated Dialogue: An Emerging Field of Museum Practice - Foteini Venieri (EXARC Journal)
The notion of dialogue is considered essential in contemporary museology. Since the 1970’s, when Cameron (1971) put forward the idea of museums as forums rather than temples, dialogue is linked to the process of democratization of museum functions and narratives and the inclusion of local communities (Sandell, 2002). Nowadays, “the idea of museum as a forum is widespread” (Kirschenblatt-Giblett, 2020). However, the term is usually vague as there is no specific content or practice related to the actual use of dialogue in museums. Recently, science and history museums are initiating facilitated dialogue-based programming to address a variety of present-day issues that affect society at large and/or local communities. As the field of facilitated dialogue-based programmes develops, questions around the aims, techniques, and challenges of such initiatives in museums emerge. This paper explores the theory and practice of facilitated dialogue in science, and history museums as well as its implications for the museum field.